(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2026)
This article explores the importance of active breaks as a strategy to counteract sedentary behavior and improve physical and emotional health in the university environment. The proposal includes the design of a web application that sends automatic reminders to students, faculty, and administrative staff to take active breaks. The application will offer personalized recommendations on activities that can be performed during these breaks, encouraging healthy habits and promoting overall well-being. This approach seeks to reduce the risks associated with prolonged inactivity, such as musculoskeletal injuries, stress, and fatigue, while improving productivity and morale in the university setting. The proposal combines technology, ergonomics, and occupational health to offer an innovative and accessible solution.